Participación de la sociedad civil en las dinámicas de innovación para el logro de los ODS. Un marco de análisis - Karen Cristina HORMECHEAS-TAPIA; Milena LEGARDA-LÓPEZ; Walter Lugo RUIZ-CASTAÑEDA; María Luisa VILLALBA-MORALES (Revista Iberoamericana de Estudios de Desarrollo, 2020)
Currently, people are beginning to recognize the contribution of innovation in the achievement of the Sustainable Development Goals (SDGs). However, the predominant approach, reduced to the economic dimension, has not focused on solving global problems. A strategy to achieve this is to take advantage of the civil society potential, which can be an active agent in the generation of innovations, which can guide them to the achievement of the SDGs. In this paper, it is proposed a framework of analysis that helps us to understand the role of civil society in the dynamics of innovation and its contribution to the achievement Agenda 2030. For this reason, this work includes an analysis of concepts about civil society, innovation, and the SDGs, which is apply to two case studies, exploring the participation of civil society in the development of innovations and its transformative potential. The results suggest that civil society is a fundamental actor for the fulfilment of the SDGs, but that, in some contexts, state intervention can be decisive for the transformative potential of socially based innovations.